Deepening our understanding of Wittgenstein - Kober, Michael (Grazer philosophische Studien ;, 2006)
This volume is of interest for anyone who aims at understanding the so-called 'later' or 'mature' Wittgenstein. Its contributions, written by leading German-speaking Wittgenstein-scholars like Hans Sluga, Hans-Johann Glock, Joachim Schulte, Eike von Savigny, and others, provide deeper insights to seemingly well discussed topics, such as family resemblance, Übersicht (perspicuous representation), religion, or grammar, or they explain in an eye-opening fashion hitherto enigmatic expressions of Wittgenstein, such as 'The pneumatic conception of thought' (PI 109), 'A mathematical proof must be su.